The teacher and the use of methods and techniques in higher education - Rocha, Aline Barros da (Seven Editora, 2023)
The challenge of educating in higher education involves discovering ways to promote and facilitate learning, aiming to prepare students for life. Whenever possible, the educator, whether in Higher Education or not, should analyze his/her pedagogical practice. The accomplishment of this research is relevant because it included adding the profile of the teacher who works in Higher Education as a mediator of the educational process, having as principles to create means of propagating learning, since creativity is an important characteristic of pedagogical work. To achieve the objectives proposed in this Article, research and bibliographical readings were carried out, with a qualitative approach. In order to know the conception of some authors about the methods and techniques used in higher education, bearing in mind that these can be considered as a dynamic factor of learning, curiosity and the challenges of investigating this topic arose. Based on the knowledge acquired in carrying out this, it was possible to verify the importance of using teaching resources in the university context, which can contribute significantly to the knowledge produced by the student. This article was an experience that served to expand knowledge about the teacher and the importance of using methods and techniques in Higher Education. DOI:https://doi.org/10.56238/sevened2023.006-007